The psychometric properties of the Chinese version internet gaming disorder scale. (July 2020) - Lei, Wei; Liu, Kezhi; Zeng, Zhen; Liang, Xuemei; Huang, Chaohua; Gong, Ke; He, Wenying; Xiang, Bo; Zhang, Jin; Zheng, Xiaojiao; Chen, Jing
Highlights: Chinese IGDSs showed good internal consistency and test-retest reliability. Scores of IGDSs correlated with impulsivity, aggression, craving for gaming and gaming hours. Dichotomous IGDS showed a sensitivity of 0.91 and a specificity of 1.00 in diagnosis of IGD. Abstract: Introduction: The study tested the psychometric properties of two Chinese version Internet Gaming Disorder scales (IGDSs): a dichotomous IGDS with yes/no type of response and a polytomous IGDS with a 0–5 Likert-type response. Methods: The reliability and validity of two scales were tested separately, among two population-based samples of Chinese adolescents and adults (351 for dichotomous IGDS and 378 for polytomous IGDS). The diagnostic accuracy of the dichotomous IGDS was assessed in an independent sample of 114 gamers (56 disordered gamers and 58 average gamers) using Receiver Operating Characteristic (ROC) analysis. Results: The results demonstrated good internal consistency (αdichotomous = 0.80 and αpolytomous = 0.89) and test–retest reliability (rdichotomous = 0.83 and rpolytomous = 0.84) for both scales. Both scales showed sound validity, as indicated by significant correlations with measurements of internet addiction, aggression, impulsivity, craving for gaming and time spent playing games. Factor analysis demonstrated that both Chinese IGDSs have a similar single-component structure to the original scales. The ROC analysis indicated an excellent diagnostic accuracy of the dichotomous IGDS. When apply the five or more cutoff points, the prevalence of IGD was 7.41% in the population-based sample. Conclusion: This study demonstrated robust psychometric properties of the Chinese version dichotomous IGDS and polytomous IGDS, and suggests that these scales are valid tools that suitable for clinical and research purposes.